Verbal Analytical Forms with Modifier ОДЫР-‘to sit’ in Khakass Language - I. L. Kyzlasova (Научный диалог, 2018)
The article deals with the semantics of the form -ып одыр in the Khakass language. It is noted that the researchers of the Turkic languages of Southern Siberia differently determine the content of the form -ып одыр : as a designation of process, durativity, continuality, actuality, etc. It is revealed that in the Khakass language the form -ып одыр denotes a specific process mode of action: in the speech mode having actual-long character, in the narrative mode combining additional characteristics (duration, generality, intensity, amplification, imperativeness, etc.), as it is the basis for the development of other meanings of imperfect. It is emphasized that the interpretation of the meanings of speech and narrative regimes in this article is in some way different from the conventional theory in the Russian language. The author considers the analytical construction -ып одыр in zero form with obvious signs of evidence as a form of speech mode, the second (with affixes) - with signs of facticity - as a form of narrative mode. It is indicated that the lexical component in the analytical construction -ып одыр are unsaturated verbs with an active causator, and the functional verb одыр- in almost all cases (except for the constructions formed from the verbs of motion) retains its lexical meaning ‘to sit’, forming a taxic-aspectual relationship of simultaneity.